qandeel-e-adab class 4 qawid-u-insha - Maqsood, Saeed (Lahore : Asian traders, 2016)
Qandeel-e-Adab: Qawaid-o-Insha for Class 4 is a book designed to teach young students the basics of Urdu grammar and composition. It covers essential topics such as sentence structure, punctuation, and vocabulary, with simple explanations and examples. The book aims to help students develop their writing skills by providing exercises and activities that promote understanding and creativity in Urdu writing. It is a helpful resource for building a strong foundation in the language at the primary school level.
Keywords: Urdu : Textbook